Capturing the Design Rationale in Model-Based Systems Engineering of Geo-Stations. (May 2022) - Zech, A.; Stetter, R.; Rudolph, S.; Till, M.
Abstract: The design rationale describes the justification of design decision or selection. To avoid unnecessary design iterations, a capturing and documentation of this rationale is highly desirable. In digital engineering processes it is of imminent importance not only to document the evaluation processes behind this rationale but to make them repeatable and digitally executable. This allows to design a variety of product variants within an engineering framework. This paper explains an approach based on graph-based design languages and presents it based on a section of an automotive assembly system.